Craniofacial identification - Wilkinson, Caroline; Rynn, Christopher; Cambridge Books Online (Online service). (Cambridge Cambridge University Press, 2012)
"The promotion of CCTV surveillance and identity cards, along with ever heightened security at airports, immigration control and institutional access, has seen a dramatic increase in the use of automated and manual recognition. In addition, several recent disasters have highlighted the problems and challenges associated with current disaster victim identification. Discussing the latest advances and key research into identification from the face and skull, this book draws together a wide range of elements relating to craniofacial analysis and identification. It examines all aspects of facial identification, including the determination of facial appearance from the skull, comparison of the skull with the face and the verification of living facial images. With sections covering the identification of the dead and of the living, it provides a valuable review of the current state of play along with the latest research advances in this constantly evolving field" -- Provided by publisher
Part I. Identification of the Living: 1. Familiar face recognition Vicki Bruce; 2. Unfamiliar face recognition Peter J. B. Hancock; 3. EFIT-V: evolutionary algorithms and computer composites Chris Solomon, Stuart Gibson and Matthew Maylin; 4. Facial recall and computer composites Charlie Frowd; 5. Facial ageing David Hunter, Bernard Tiddeman and David Perrett; 6. Age progression and regression Joe Mullins; 7. Automated age progression Stuart Gibson; 8. Facial recognition from identification parades Catriona Havard and Amina Memon; 9. Virtual line-ups Kathryn Y. Segovia, Jeremy N. Bailenson and Carrie Leonetti; 10. Computer-generated face models Bernard Tiddeman; 11. Recognising faces in motion Karen Lander and Natalie Butcher; 12. Facial image comparison Josh P. Davis, Tim Valentine and Caroline Wilkinson; 13. Three-dimensional facial growth and imaging Stephen Richmond, Alexei Zhurov and Arshed Toma; Part II. Identification of the Dead: 14. Post-mortem prediction Caroline Wilkinson and Amy Tillotson; 15. Manual facial reconstruction Ludo Vermeulen; 16. The relationship between the face and the skull Christopher Rynn, Tatiana Balueva and Elizaveta Veselovskaya; 17. Automated facial reconstruction Dirk Vandermeulen, Peter Claes, Sven De Greef, Guy Willems, John Clement and Paul Suetens; 18. Computer-generated facial depiction Gregory Mahoney and Caroline Wilkinson; 19. Craniofacial superimposition Mineo Yoshino; 20. Juvenile facial reconstruction Caroline Wilkinson; Index
Title from title screen (viewed on November 13, 2023)
Also issued in print format
Mode of access: World Wide Web
Keywords: Facial reconstruction (Anthropology); Face -- Identification; Face -- Imaging; Biometric identification